2017
DOI: 10.1177/1367493517727070
|View full text |Cite
|
Sign up to set email alerts
|

Age-appropriate preparations for children with cancer undergoing radiotherapy: A feasibility study

Abstract: The aim of this study was to test age-appropriate information and preparation procedures for children with cancer undergoing radiotherapy (RT) for feasibility and effectiveness in terms of the need for general anesthesia (GA) and anxiety. In a quasi-experimental controlled clinical trial, 17 children aged 3-18 years receiving age-appropriate preparation were compared with 16 children in a control group. Feasibility in terms of recruitment, compliance, and acceptability was assessed. Effectiveness was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Other studies have demonstrated the utility of playful 12,13,15,16 or narrative 12 tools to give children a better idea of what the treatments entail, and some have highlighted the importance of video‐based cognitive‐behavioral interventions 1,14,16 . In short, research suggests that a personalized approach is needed, recognizing the needs of each child, 2 but it is equally important to involve a multidisciplinary team 8,15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated the utility of playful 12,13,15,16 or narrative 12 tools to give children a better idea of what the treatments entail, and some have highlighted the importance of video‐based cognitive‐behavioral interventions 1,14,16 . In short, research suggests that a personalized approach is needed, recognizing the needs of each child, 2 but it is equally important to involve a multidisciplinary team 8,15 …”
Section: Discussionmentioning
confidence: 99%
“…Younger children especially may have difficulty coping with these procedures, and their compliance can be hindered by anxiety and agitation. Their reaction can be associated with several different causes, including the unfamiliar nature of the procedure and the surrounding environment (the lighting and the sounds produced by the equipment), being isolated in the therapy bunker without a parent for at least 15 min, having to wear a thermoplastic head immobilization mask in the case of brain tumors, and sometimes prior experience of frightening medical maneuvers 1,2 . Compliance problems may affect not only younger children under 3 years old, but older patients too, especially if they have cognitive impairments, or become agitated due to a lack of containment, or very distressed when away from their parents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the total score of F ("psychological interview" and the items in group E, the CEMS scale, had a strong impact on our schedule. The CEMS has been validated (26) and is already used in the field of pediatric radiotherapy (27). Recording patients' distress on entering the bunker for the first time helps the clinician and psychologist to immediately ascertain the complexity of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some children need daily anesthesia to cope with the procedure, lasting for several weeks and accompanied by fasting periods; this is suboptimal for a growing body [ 6 ]. It has been suggested that with the right preparation children may have a greater chance of coping with the RT procedure, allowing them to receive the treatment without sedation [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%